La crise de biodiversité à l’épreuve de l’action publique néolibérale - Clémence Guimont; Rémy Petitimbert; Bruno Villalba (Développement Durable et Territoires)
This text introduces the special section « Biodiversity loss, New Public Management and neoliberalism ». It analyzes the effects and the consequences of neo-managerial management of biodiversity in a context of ecological emergency. This introduction allows to question the policy implementation of biodiversity crisis starting from what the neoliberal rationality makes it possible to apprehend it. The discussion aims at interrogating the framing of the crisis and the instrumentation performed within the administration. It is then the capacity of neoliberal rationality to respond to the biodiversity crisis that is ultimately questioned.